The Influence Of Relationship Bonds, Trust And Service Quality On Customer Loyalty Through Commitment Variables At Rural Credit Banks In Central Jawa - Zailani, Abdullah; -, Budiyanto; -, Djawoto (Indonesian Journal Publisher, 2024)
Research This carried out at BPR Central Java with Population in study this is​ all over individual BPR customers, who use service banking from BPR above will alone; good savings, checking account and credit spread across 32 BPR offices located in Central Java. With amount sample as many as 320 respondents. Retrieval technique sample in study This use accidental sampling technique. Analysis technique in study This use technique analysis SEM with AMOS 5 (Analysis of Moment Structure) and SPSS version 20.0 program packages. From the results testing hypothesis show that Hypothesis First No significant, that bond connection influential towards loyalty customers. This means that it is getting closer bond the relationship that occurs between Customer with company BPR banking, no always increase loyalty customers, The second hypothesis is significant, that trust has an effect on customer loyalty. The higher the level of customer trust does not necessarily have an implication on increasing the loyalty of BPR banking customers, The third hypothesis is significant, that service quality has an effect on customer loyalty. The better the quality of service to customers does not necessarily have an implication on increasing the loyalty of BPR banking customers, The fourth hypothesis is significant, that the relationship ties have an effect on Commitment. The closer the relationship ties between customers and BPR financial institutions have implications for increasing BPR banking Commitment, The fifth hypothesis is significant, that trust has an effect on Commitment. The higher the customer trust in BPR financial institutions has implications for increasing BPR banking Commitment, The sixth hypothesis is significant, that service quality has an effect on Commitment. The higher the customer trust in BPR financial institutions has implications for increasing BPR banking Commitment, The seventh hypothesis is significant, that commitment has an effect on customer loyalty. The higher the Commitment to BPR financial institutions has implications for increasing BPR banking customer loyalty, Hypothesis eighth significant, m proves that the commitment mediate in full bond influence connection towards loyalty Customer from the results of the Sobel test. Commitment mediate in a way full influence between bond connection to loyalty customers, meaning the interaction between the bonds connection with commitment will improve loyalty Customers , Hypothesis ninth significant , m proves that the commitment partially mediate the influence of trust towards loyalty Customer from the results of the Sobel test. Commitment mediate in a way partial influence between trust to loyalty customers, meaning the interaction between trust with commitment will improve loyalty Customers, Hypothesis tenth significant, m proves that the commitment partially mediate the influence of quality service towards loyalty Customer from the results of the Sobel test. Commitment mediate in a way partial influence between quality service to loyalty customers , meaning the interaction between quality service with commitment will improve loyalty customers.